Prinsip-Prinsip Negara Hukum Modern dalam Pendekatan Hukum Islam - Agus Mahfudin (Proceedings of Annual Conference for Muslim Scholars, 2018)
Islamic law has its own characteristics, sources and order of laws and legislation. Through this characteristic will present nine general principles about the state of law in the approach of Islamic law. The principle of power as a mandate, in Islam power is a mandate. The principle of musyawarah which is a constitutional principle in Islamic law that must be implemented in a government. The principle of justice in Islamic law contains a concept of high value. The principle of equality which is the pattern of Islam and therefore it is the core of its sovereignty. Principles of recognition and protection of human rights. The principle of free justice that should not be contrary to the objectives of Islamic law. In implementing the judicial principle free of judges must also consider the principle of trust. The principle of peace in Islamic law must be established on the basis of the principle of peace. Relations with other countries must be woven and adhering to the principle of peace. The principle of welfare in Islamic Law aims at realizing social justice and economic justice for all members of society. The principle of obedience implies that all the people without exception are obliged to obey the government.